Flow and foreign direct investment to hitherto neglected developing countries - Oluyele Akingube (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
The last decade or so has witnessed rather dramatic increases in the flow of foreign direct investment (FDI) to the developing countries of the world. However, the balance of evidence seems to point in one direction, the inflow has been uneven. Middle-income developing countries have benefited from this upsurge at the expense of the lower-income countries. In an attempt to explore the two complimentary issues involved in FDI flows, we adopted the two-part econometric approach in which a Probit model was first estimated in order to examine the binary issue of whether or not to locate FDI in hitherto neglected developing countries. In the second step, a panel regression model was employed to examine the factors that may explain the volume of FDI to further allocate to existing FDI-receiving countries. Our findings reveal that a combination of high per capita income, outward-orientation to international trade, a high level of infrastructure development and a high rate of return on investment are the significant decision parameters in the two-part aggregate investors' behaviour analyses.
Keywords: F21; F23; 330; neglected developing countries; foreign direct investment; two-part econometric modelling; panel data analysis; Direktinvestition; Entwicklungsländer